Dark fermentative hydrogen production and transcriptional analysis of genes involved in the unicellular halotolerant cyanobacterium Aphanothece halophytica under nitrogen and potassium deprivation - Nattanon Chinchusak; Aran Incharoensakdi; Saranya Phunpruch (Frontiers in Bioengineering and Biotechnology, 2023)
production under dark anaerobic condition in both nitrogen- and potassium-deprived cells.
Keywords: Algal biology and biofuel production; Photosynthetic Processes and Mechanisms; Microbial Community Ecology and Physiology